ACCOUNTING PROCESS - Rustam Farmonovich Omanov (American Journals, 2023)
Presently for shareholders and other users the financial statements are based on accounting principles and rules that are passed from country to country, in some cases only in one country. Thus, there may be a lack of comparability in the accounting reports. The disadvantage of this situation is that investment analysts and other users who use the financial report have to incur additional costs in the process of analyzing the report because it is structured according to different standards. They may also encounter confusion in the interpretation of reports. As a result of this process, effective competition in the global capital market will deteriorate, and companies will have to bear the high cost of maintaining capital. Most importantly, different amounts of profit for different countries can lead to a loss of confidence in the financial statements.
Keywords: Procedure for harmonization, accounting standards, financial reporting, accounting system, management accounting..